Hydrogeology of salt karst under different cap soils and climates (Persian Gulf and Zagros Mts., Iran) - Jiri Bruthans; Jiri Kamas; Michal Filippi; Mohammad Zare; Alan L. Mayo (International Journal of Speleology, 2017)
Southern Iran hosts abundant salt karst phenomena in numerous salt diapirs. This paper provides a new insight into the relationships among climate, cap soil and salt karst hydrogeology. Cave systems were documented and mapped. Soil, drip, stream, and flood waters from different environments were studied at several diapirs. It was revealed that the soil water chemistry depends on both the climate and cap soil thickness. In semi-arid climates, a thick cap soil forms (>3 m) and water has very low TDS values (0.15 g/l). In arid climates, a shallow cap soil forms, and soil water is gypsum-saturated with low dissolved halite contents. In both environments, drip waters from salt caves and springs displayed high TDS values (255 to 347 g/l). This is explained by the dissolution of halite and minor anhydrite/gypsum, a K-Mg sulfate and sylvite. Spring water plots on a local meteoric water line, whereas drips in caves have an evaporative signature. The flash flood runoff is dominated by event rain water based on isotopic data, while springs are dominantly supplied by a base flow component. The mean residence time of water on the diapirs is controlled by the cap soil thickness. Water residence times may reach several hundreds of years on a thick cap soil based on an exponential model butsoil.